2017
DOI: 10.2147/ijwh.s106107
|View full text |Cite
|
Sign up to set email alerts
|

Osteosarcopenic obesity in women: impact, prevalence, and management challenges

Abstract: Osteosarcopenic obesity syndrome (OSO) has recently been identified as a condition encompassing osteopenia/osteoporosis, sarcopenia and obesity. OSO is especially deleterious in older adults (even if they are not obese by conventional measures), due to age-related redistribution of fat and its infiltration into bone and muscle. Osteoporosis and bone fractures in elderly increase the risk of sarcopenia, which, through decreased mobility, increases the risk of more falls and fractures, creating a vicious cycle. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
1
10

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(92 citation statements)
references
References 89 publications
(131 reference statements)
3
78
1
10
Order By: Relevance
“…A recent analysis of National Health and Nutrition Examination Survey (NHANES) data 234:1 revealed that energy imbalance, lower protein intakes, high level of simple carbohydrates and low omega-3 (n-3) PUFA may contribute to osteosarcopenic obesity syndrome (Kelly et al 2017). This analysis confirmed the paradox regarding energy intake: the latter is reduced with aging in both men and women and across all survey years, yet there is a gain in weight with aging.…”
Section: Changes In Dietary Intake and Nutrient Requirements With Agingmentioning
confidence: 79%
See 3 more Smart Citations
“…A recent analysis of National Health and Nutrition Examination Survey (NHANES) data 234:1 revealed that energy imbalance, lower protein intakes, high level of simple carbohydrates and low omega-3 (n-3) PUFA may contribute to osteosarcopenic obesity syndrome (Kelly et al 2017). This analysis confirmed the paradox regarding energy intake: the latter is reduced with aging in both men and women and across all survey years, yet there is a gain in weight with aging.…”
Section: Changes In Dietary Intake and Nutrient Requirements With Agingmentioning
confidence: 79%
“…As aging uniquely influences many physiological functions, the most observable are those regarding body composition changes, including loss of bone, loss of muscle mass and strength, and increased body fat leading to osteosarcopenic obesity syndrome (Ilich et al 2014b, JafariNasabian et al 2017. These changes in body phenotype will be discussed in this review, addressing also the hormonal influences and cellular mechanisms leading to tissue and whole-organism changes.…”
Section: :1mentioning
confidence: 99%
See 2 more Smart Citations
“…Based on evidence for an increase in not only bone adiposity but also muscle adiposity with osteoporosis and aging, Ilich and colleagues further suggested the idea of obesity (as an accumulation of fat rather than overall body mass index [BMI]) within bone and muscle, termed osteosarcopenic obesity . JafariNasabian and colleagues further noted the potential of this source of fat to generate pro‐inflammatory cytokines and other endocrine players to contribute toward the deterioration of bone and muscle . However, no studies have drawn a link between muscle adiposity and bone adiposity in the context of osteoporosis, making the present investigation a unique approach to better understanding part of the bone‐muscle interactions paradigm.…”
Section: Introductionmentioning
confidence: 99%